True Fibroma of Alveolar Mucosa - Shankargouda Patil; Roopa S. Rao; Sanketh Sharath; Anveeta Agarwal (Case Reports in Dentistry)
Benign fibrous overgrowths are often found in the oral cavity, almost always being reactive/irritational in nature. However, benign mesenchymal neoplasms of the fibroblasts are extremely uncommon. Here we report a case of “True Fibroma of Alveolar Mucosa” for its rarity.